Synthesis and Antibacterial Activity of New Chiral Aminoalcohol and Benzimidazole Hybrids - ABDURRAHMANOĞLU, SUZAN (WILEY-V C H VERLAG GMBH, 2020)
New chiral aminoalcohol-benzimidazole hybrids have been synthesized from commercially available aminoalcohols [S(+)-Phenylglycinol, S(-)- Phenylalaninol and S(+)- Leuicinol] and 2-(chloromethyl)-N-tosyl-1-H-benzimidazole. The synthesized compound were characterized by IR, NMR, and LC-MS analysis. The antibacterial properties of aminoalcohol-benzimidazole hybrid molecules 4 a, 4 b, and 4 c were investigated against both gram (+ve) and gram (-ve) bacterial pathogens by the well-diffusion method using several standarts. The cell-based biological experiment was consistent with in silico studies. Furthermore, in silico studies revealed that all synthesized compounds could be suggested as potential drugs for inhibition of both peptide deformylase for bacteria and sterol 14 alpha-demethylase for yeast.
Keywords: Benzimidazole; Antibacterial Agent; Aminoalcohol; PDF inhibitor; Molecular docking; PEPTIDE DEFORMYLASE; DERIVATIVES; POTENT; DISCOVERY; DESIGN; BACTEREMIA; SERIES